2022
DOI: 10.1021/acsomega.1c06022
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Magnetic Carbon Nanofiber Derived from Bacterial Cellulose for the Removal of Diclofenac from Water

Abstract: Engineering and synthesis of novel materials are vital for removing emerging pollutants, such as pharmaceuticals from contaminated water. In this study, a magnetic carbon nanofiber (MCF) fabricated from bacterial cellulose was tested for the adsorption of diclofenac from water. The physical and chemical properties of the synthesized adsorbent were examined by field emission scanning electron microscopy (FESEM), field emission transmission electron microscopy (FETEM), X-ray diffraction (XRD), Brunauer–Emmett–Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…MCF is a porous (mesopores and macropores) material having a specific surface area of 222.3 m 2 /g. The diclofenac elimination was effective (93.2%) and quick (20 min) [66]. Self-assembling two-dimensional graphene oxide nanosheets and one-dimensional carbon nanotubes were used to readily construct three-dimensional macrostructures.…”
Section: Adsorption For Ec Removalmentioning
confidence: 99%
“…MCF is a porous (mesopores and macropores) material having a specific surface area of 222.3 m 2 /g. The diclofenac elimination was effective (93.2%) and quick (20 min) [66]. Self-assembling two-dimensional graphene oxide nanosheets and one-dimensional carbon nanotubes were used to readily construct three-dimensional macrostructures.…”
Section: Adsorption For Ec Removalmentioning
confidence: 99%
“…Nanocellulose-based materials can also be used to treat wastewater contaminated with hazardous organic pollutants, including dyes, pharmaceutical compounds, and petroleum products [ 292 , 316 , 317 , 318 , 319 , 320 ]. For example, Wang et al reported a new superabsorbent aerogel based on BC and graphene oxide, which showed excellent absorption property of organic liquids [ 316 ].…”
Section: Bc-based Nanocompositesmentioning
confidence: 99%
“…The development and synthesis of new materials is vital to the removal of new contaminants, such as pharmaceuticals, from polluted water. Ieamviteevanich et al developed a magnetic carbon nanofiber derived from BC to remove diclofenac from water [ 320 ]. Diclofenac is one of the non-steroidal anti-inflammatory drugs widely used to treat acute and chronic pain in humans and animals.…”
Section: Bc-based Nanocompositesmentioning
confidence: 99%
“…Nanofibers sourced from natural feedstocks have been drawing attention in the chemistry, physics, materials, and engineering research community for their unprecedented properties from their non-linearized nanoscopic dimensions [1][2][3][4]. For example, they have been found to significantly improve mechanical strengths, endow non-linear optics, and provide very high surface area compared tot their bulk analogues.…”
Section: Introductionmentioning
confidence: 99%
“…1 Chitin 25 = 25 passes, 2 NPCS = Non-Protein Crustacean Shell 14 passes, 3 CSAM 14 = Crustacean Shell Control 14 passes,4 CSAM 25 = Crustacean Shell Control 25 passes; all reported data within ±0.05 standard deviation in a 95% confidence interval.…”
mentioning
confidence: 99%